ANTIOXIDANT ACTIVITY TEST OF GUAVA LEAVES ETHANOL EXTRACT (Syzygium aqueum Burm F) WITH DPPH METHOD (1,1-Diphenyl-2-picrylhydrazil) - Fina Fitriani; Siti Nur Hikmah; Fawwaz Muhammad Fauzi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Free radicals are compounds that can cause damage to human body cells, which can be prevented with antioxidants. Antioxidants can be found in several natural ingredients, such as water guava leaves. This study aims to determine the antioxidant activity of an ethanol extract from water guava leaves (Syzygium aqueum Burm F). The water guava leaves used came from the Kempek Palimanan Cirebon area. Extraction was carried out using the maceration method using a 96% ethanol solvent until a concentrated extract was obtained. The extract was identified for secondary metabolite content using a reagent test. An antioxidant activity test was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Analysis of the strength of antioxidant activity is carried out by calculating the IC50 value, which is based on the percent inhibition of free radicals by the test sample by comparing Vitamin C. Identification of active compounds in the concentrated ethanol extract of water guava leaves indicated the presence of flavonoids, alkaloids, saponins, and tannins. The antioxidant activity of an ethanolic 96% extract of water guava leaves (Syzygium aquarium) in this study had an IC50 value of 6.89 ppm, which shows very strong antioxidant activity in warding off free radicals. Keywords: antioxidants, water guava leaves, DPPH